Catalytic oxidation of toxic organics in aqueous solution for wastewater treatment - Saputra, Edy (Curtin University, 2013)
This research focuses on catalytic oxidation of toxic organics in aqueous solution for wastewater treatment. Manganese-based catalysts such as MnO, MnO2, Mn2O3, and Mn3O4, Mn2O3@MnO2 have been synthesized, characterized, and tested in heterogeneous activation of peroxymonosulfate for phenol degradation in aqueous solution. It was found that phenol degradation on the various catalysts followed first order kinetics. The operational parameters, such as catalyst and peroxymonosulfate loadings, phenol concentration, and temperature, were also investigated for optimal phenol degradation efficiency.